Dispute Resolution Effectiveness and Settlement Rates in the Katarungang Pambarangay System in General Santos City - Sarael, Gladice; Garcia, Beverly (International Journal of Sustainability and Advanced Integrated Research, 2026)
The Katarungang Pambarangay (KP) system serves as a legally mandated, community-based framework in the Philippines designed to resolve local conflicts through mediation, conciliation, and arbitration. This study aimed to evaluate the system’s dispute resolution effectiveness—specifically across the dimensions of implementation, performance, and compliance—and analyze objective settlement rates in the six highest-volume barangays of General Santos City from 2020 to 2024. Utilizing a Descriptive and Correlational research design, the study gathered primary data from 84 currently serving Lupon Tagapamayapa members selected through proportionate sampling. Data collection employed a dual-component approach: a modified survey questionnaire using a 4-point Likert scale to measure perceived effectiveness and a systematic document review of annual case records provided by the respective Lupon clerks. Statistical analysis involved weighted means for descriptive data and Spearman’s Rank Correlation for inferential testing. The findings indicated that the KP system in selected barangays of General Santos City operates at a "Very High/Excellent" level of effectiveness across all measured dimensions: Compliance achieved the highest overall mean (3.9), followed by Implementation (3.8) and Performance (3.7). Moreover, settlement rates were robust, ranging from 76.10% in Barangay Calumpang to a perfect 100% in Barangay San Isidro. Inferential analysis revealed significant positive relationships between all effectiveness indicators and successful settlement outcomes. Compliance with legal procedures was identified as the strongest driver of successful settlements (r=0.385,p=0.000), suggesting that strict adherence to mandated legal protocols is more influential than individual mediator qualifications alone. The study concludes that the KP system in General Santos City successfully fulfills its mandate to decongest formal court dockets by resolving most disputes at the grassroots level. Recommendations focus on strengthening systematic recording systems and institutionalizing regular specialized training for Lupon members to sustain their high level of procedural integrity and legal mastery.
Keywords: Katarungang Pambarangay, Dispute Resolution, Settlement Rates, General Santos City, LuponTagapamayapa, Procedural Compliance